Litter Dynamics and Nutrient Return of Poplar Plantations in Moist Plain Areas of Central Himalayas - Lodhiyal, L. S.; Lodhiyal, Neelu; Singh, Sanjay K. (Indian Forester, 2002)
This paper deals with forest floor biomass of 5-9 years old pure Poplar plantations litter fall and nutrient content return through the litters of poplar plantations in moist plain area (Tarai belt) of Central Himalayas. The tree density was 400 trees ha-1 for each stand. However, the basal area of stand ranged from 18.8 (5-yrs) to 34.2 m ha-1 (9-yrs). The total mean forest floor biomass ranged from 3.44 t ha-1 in the 5-yrs old to 5.43 t ha-1 in the 9 yrs-old poplar plantations. In different seasons, it was in order: winter (5.70-8.74 t ha-1) > summer (3.91-6.05 t ha-1) > rainy season (0.72-1.51 t ha-1). However, the forest floor biomass across seasons increased with increase in age of poplar plantations. The total litter fall was 6.38 t ha-1 yr-1 in the 5 yrs old to 9.87 t ha-1 yr-1 in the 9 yrs-old plantations. Of this, leaf litter had maximum 79 (9-yrs) to 81 % (5 yrs-old) stand. The annual replacement of forest floor litter biomass ranged from 89% (in 9-yrs) to 94% (in 5-yrs-old). However, the turnover rate ofnutricnts (NPK) was 71-89%. The total amount of nutrient return through litter was 79-117 kg ha-1yr-1 N, 9-17 kg ha-1 yr-1 P and 46-61 kg ha -1 yr-1 K. It was increased with increase in plantation age because of higher amount of litter. The nutrient use efficiency ranged from 81-84 for N, 694-723 for P and 138-162 for K.